Development of a mathematical model of scrambler-type speech-like interference generator for system of prevent speech information from leaking via acoustic and vibration channels - Blintsov, Volodymyr; Nuzhniy, Sergey; Kasianov, Yurii; Korytskyi, Viktor (Technology audit and production reserves, 2019)
The protection of speech information is one of the main tasks of information protection and is a sign of a responsible attitude of an organization (company) both to its information resources and respect for partners. The object of research is the process of protecting speech information from leakage by acoustic and vibrational technical channels at the objects of information activity. An exceptional feature of such facilities is the circulation, processing and discussion of issues containing information of limited access, including state secrets. A peculiarity of Ukraine is the requirement to use exclusively technical means that have passed the relevant certification at such facilities. The basis of the active noise jamming system is a noise generator. At the same time, one of the most problematic issues is that in Ukraine only noise interference generators of the “white” noise type and its clones are allowed to be used. The systems have a number of significant drawbacks – the low protection level of intercepted speech signals from noise filtering (interference), a significant noise level in the premises to be protected, and others. A block diagram of an interference generator is proposed. And its mathematical model is also developed and researched in Matlab. In the course of the research, a comparative analysis of the signals input and synthesized by the generator was carried out, their temporal and spectral characteristics were investigated. The obtained results indicate the high efficiency of the proposed method of protecting speech information. This is due to the fact that the method of forming a speech-like interference has a number of features that provide a significant destructive effect on speech information, namely the use of a combined scrambler model with time and frequency transforms. The method takes into account the use of dynamic keys for coding systems, and the connection of third-party sources of speech signals, as well as ringing (mixing of the input and output signals) at the input of the scrambling unit. This decision excludes reengineering. The results are confirmed by the research of an experimental sample. The destructive effect of typical noise interference («white» noise and its clones) and the noise interference created by the proposed method are compared by the criterion of residual speech intelligibility of the speaker’s speech. Studies have shown that, provided that no more than 10 % of the level of residual intelligibility is provided, the volume level of the output signal of the noise interference generator can be reduced by almost 6 dBA.